Hepatitis B in pregnancy. Issue 2 (17th October 2013) - Dyson, Jessica Katharine; Waller, Julia; Turley, Andrena; Michael, Enid; Moses, Samuel; Valappil, Manoj; Hudson, Mark; Bassendine, Margaret; McPherson, Stuart
Abstract : Objective: Vertical transmission of the hepatitis B virus (HBV) is the commonest mode of infection and can be prevented with immunoprophylaxis of the infant and antiviral therapy in the mother. Our aim was to review a cohort of subjects with HBV in pregnancy to determine the prevalence of active disease or high HBV-DNA levels that required treatment to prevent transmission, and to review the management of mothers and infants. Methods: A retrospective case-note review was conducted of all the HBV-infected pregnant women and their infants who attended the Newcastle obstetric services from 2007 to 2011. Results: There were 113 pregnancies in 81 women (median age 28 years; 15% hepatitis B e antigen (HBeAg) positive) during 2007–11. 71% of mothers were first diagnosed with HBV during pregnancy. The mothers were born in 28 different countries. 69% of mothers had an HBV-DNA level less than 2000 IU/mL and 13% had HBV-DNA levels greater than 1.0×10 7  IU/mL so would be eligible for antiviral therapy to prevent transmission to the infant. 9% had active eAg-positive HBV and 3% had active eAg-negative HBV requiring treatment. All infants born to HBeAg-positive mothers received hepatitis B immunoglobulin (HBIG) appropriately and 76% of infants received a full HBV vaccination course. One infant born to an HBeAg-negative mother was hepatitis B surface antigen positive 1 year post-delivery. Conclusions: One in six women had active HBV requiring treatment or high HBV-DNA levels that would benefit from antiviral treatment to reduce the transmission risk. HBIG was administered appropriately but completion of the vaccination course was suboptimal.